Youla Parameterization Based Adaptive Controller Design for Fault Tolerant Control. Issue 1 (26th September 2012) - Cui, Lei; Zhang, Yong; Yang, Ying
Abstract A new adaptive controller for fault tolerant control (FTC) is proposed in this paper. It is realized by adapting the reconfigurable fault parameterized matrix with the estimated fault. The proposed approach is applied in a linear reduced order aircraft model, and simulation results show the effectiveness.